Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1016/j.concog.2013.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Mind experience sampling in typical adults

Abstract: We explored the frequency with which typical adults make Theory of Mind (ToM) attributions, and under what circumstances these attributions occur. We used an experience sampling method to query 30 typical adults about their everyday thoughts. Participants carried a Personal Data Assistant (PDA) that prompted them to categorize their thoughts as Action, Mental State, or Miscellaneous at approximately 30 pseudo-random times during a continuous 10-hr period. Additionally, participants noted the direction of their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 43 publications
(43 reference statements)
3
18
0
Order By: Relevance
“…As noted above, some (e.g., Alderson-Day & Fernyhough, 2014;Krueger et al, 2014), have suggested that pristine inner experience can be effectively investigated by other techniques including typical (non-DES) sampling methods and questionnaires. We now explore that suggestion by comparing and contrasting DES with a typical experience sampling study (Bryant, Coffey, Povinelli, & Pruett, 2013, which uses ESM to explore Theory of Mind) and with a typical questionnaire (the Varieties of Inner Speech Questionnaire, VISQ, McCarthy-Jones & Fernyhough, 2011). We use these studies as convenient ''laboratory specimens'' that we can dissect in the service of gaining an understanding of general principles.…”
Section: Comparing Des Esm and Questionnairesmentioning
confidence: 97%
See 1 more Smart Citation
“…As noted above, some (e.g., Alderson-Day & Fernyhough, 2014;Krueger et al, 2014), have suggested that pristine inner experience can be effectively investigated by other techniques including typical (non-DES) sampling methods and questionnaires. We now explore that suggestion by comparing and contrasting DES with a typical experience sampling study (Bryant, Coffey, Povinelli, & Pruett, 2013, which uses ESM to explore Theory of Mind) and with a typical questionnaire (the Varieties of Inner Speech Questionnaire, VISQ, McCarthy-Jones & Fernyhough, 2011). We use these studies as convenient ''laboratory specimens'' that we can dissect in the service of gaining an understanding of general principles.…”
Section: Comparing Des Esm and Questionnairesmentioning
confidence: 97%
“…We now examine the procedure of a typical non-DES experience sampling study, using as an example the Bryant et al (2013) study of Theory of Mind. Bryant and colleagues use the Experience Sampling Method (ESM), which we schematize in the ''ESM'' column of Table 1.…”
Section: Typical (Non-des) Experience Samplingmentioning
confidence: 99%
“…2 Recently, Bryant, Coffey, Povinelli, and Pruett (2013) have carried out a pioneering study using the experience sampling method to investigate the frequency of mental state attributions in contrast to behavioral attributions and miscellaneous thoughts. Bohl (2014) proposes a more specific hypothesis concerning the frequency and function of mindreading, which could be tested by the method of experience sampling.…”
Section: How ''Rarely'' Do We Actually Mindread?mentioning
confidence: 99%
“…Scientific data on this topic are very scarce. As of now, there is only one published scientific study on the phenomenology of social cognition, and it does not address the reliability of phenomenology (Bryant, Coffey, Povinelli, & Pruett Jr, 2013). Thus, we must look elsewhere for evidence on the reliability of phenomenology of social cognition.…”
Section: The Reliability Of Phenomenologymentioning
confidence: 99%
“…It is worth discussing the results of the one empirical study on the phenomenology of social cognition (Bryant et al, 2013). This study, by Lauren Bryant and colleagues, employs Descriptive Experience Sampling (DES) to investigate how often subjects consciously find themselves thinking about others' mental states.…”
Section: The Reliability Of Phenomenologymentioning
confidence: 99%